Deliberative theory and deconstruction a democratic venture - Gormley, Steven (Edinburgh University Press, 2020)
Our political climate is increasingly characterised by hostility towards constructed others. Gormley answers the question: what does it mean to do justice to others? In developing this account, he places deliberative theory and deconstruction into critical conversation with the work of Mouffe, Aristotle, Rorty, Laclau and critical theory.